SOSIALISASI ORANGTUA SEBAGAI PENDAMPING UTAMA DALAM PENDIDIKAN ANAK DI RUMAH - Subagiharti, Heni; Nasution, Atikah Rahmah; Rambe, Nurhaliza Amria; Antika, Tari; Rahmi, Sofia; Marpaung, Novi Indriani; Aurel, Silvia; Alfath, Nurhalizah (Smart Education, 2024)
This service activity aims to invite parents and children to participate in fostering good relationships at home, both parents as the main pillars in building children's education at home. This service activity uses a descriptive method using a qualitative approach. In this service activity, the data collection techniques used are observation, interviews and documentation. The result of this service is that the community in Sidodadi sub-district has a better understanding of the importance of the role of parents in children's education at home, involvement in children's education at home, can increase children's motivation and learning outcomes so that there is an increase in education in Sidodadi sub-district, such as increasing student achievement, increasing student participation in learning activities and increasing student interest in learning.Keywords: Parents, Children's Education, Students